A comparative study of saline infusion sonohysterography and hysterosalpingography for evaluation of female infertility - Bhattacharya, Riya; Ramesh, A. C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is a complex disorder with significant psychological and emotional impact. It affects 10-15% of couples in the reproductive age group. Hence, evaluation of female genital tract is an important part of workup of an infertile woman. The most commonly used methods are hysterosalpingography which exposes the patient to ionizing radiation and laparoscopy which is invasive. This calls for the need of a low risk method that would be suited for ambulatory application. Saline infusion sonohysterography is a cost-effective, safe, non-invasive and a rapid procedure to visualize the female pelvic organ in evaluation of infertility. The objective of this study was to compare diagnostic accuracy of saline infusion sonography (SIS) over conventional hysterosalingography (HSG) for evaluation of female infertility. Methods: Total 50 patients who presented to the gynecology OPD between 2018 to September 2019 for evaluation of infertility were included for the study. The results of the two procedures were compared. Results: For evaluation of uterine cavity, SIS had a sensitivity of 95%, specificity of 100%, PPV of 100%, NPV 75% and a sensitivity of 100%, specificity of 100%, PPV of 91%, NPV of 100% for tubal patency as compared to HSG. Conclusions: For evaluation of uterine cavity, SIS had a sensitivity of 95%, specificity of 100%, PPV of 100%, NPV 75% and a sensitivity of 100%, specificity of 100%, PPV of 91%, NPV of 100% for tubal patency as compared to HSG.